Concierge: Personal database software for managing digital research resources - Sakai, Hiroyuki; Aoyama, Toshihiro; Yamaji, Kazutsuna; Usui, Shiro (Frontiers in Neuroinformatics, 2007)
This article introduces a desktop application, named Concierge, for managing personal digital research resources. Using simple operations, it enables storage of various types of files and indexes them based on content descriptions. A key feature of the software is a high level of extensibility. By installing optional plug-ins, users can customize and extend the usability of the software based on their needs. In this paper, we also introduce a few optional plug-ins: literaturemanagement, electronic laboratory notebook, and XooNlps client plug-ins. XooNIps is a content management system developed to share digital research resources among neuroscience communities. It has been adopted as the standard database system in Japanese neuroinformatics projects. Concierge, therefore, offers comprehensive support from management of personal digital research resources to their sharing in open-access neuroinformatics databases such as XooNIps. This interaction between personal and open-access neuroinformatics databases is expected to enhance the dissemination of digital research resources. Concierge is developed as an open source project; Mac OS X and Windows XP versions have been released at the official site (http://concierge.sourceforge.jp).